2001
DOI: 10.1051/agro:2001105
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium toxicity in plants: a review

Abstract: Aluminium toxicity and problems concerning tolerance and ecological performance are discussed briefly. Differential tolerance of plant genotypes to aluminium stress is a more promising approach to increase our understanding of aluminium tolerance in plants. Induction of Al tolerance and its characterization are also reviewed. The cytogenetic effects of aluminium on plants are discussed in depth. Efforts have been made to compare the relative sensitivity of various plant species including micro-and macro-flora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
180
0
17

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(203 citation statements)
references
References 151 publications
6
180
0
17
Order By: Relevance
“…Al was also reported to bind with phospholipids of the cell membrane that influences the ion channel proteins that inhibits specific ions flux. Ammonium (NH 4 ), of those is a positive modulator for CAT activity and thus it's scarcity under Al contamination particularly in acid soil might set a limitation for optimum activity (Rout et al 2001). It is also noted that the isozymic profiles of CAT had significant alteration in plants of the present experiment when treated with Put under Al stress as compared to control.…”
Section: Discussionmentioning
confidence: 49%
“…Al was also reported to bind with phospholipids of the cell membrane that influences the ion channel proteins that inhibits specific ions flux. Ammonium (NH 4 ), of those is a positive modulator for CAT activity and thus it's scarcity under Al contamination particularly in acid soil might set a limitation for optimum activity (Rout et al 2001). It is also noted that the isozymic profiles of CAT had significant alteration in plants of the present experiment when treated with Put under Al stress as compared to control.…”
Section: Discussionmentioning
confidence: 49%
“…It means that aluminum was most promotive at low concentration but showed adverse effects at high concentration. Rout et al, (2001) found that aluminum did not affect the seed germination but helped in new root development and seedling establishment. Neogy et al, (2000) found that aluminum toxicity was major deterrent for plants growth in acid soils.…”
Section: Discussionmentioning
confidence: 96%
“…No entanto, pouca atenção tem sido dada à presença de elementos tóxicos no meio que serve de substrato para as sementes. O alumínio é um elemento que se torna disponível em condições de pH baixo, sendo que, em solo ácido, o elemento solubilizase em Al 3+ , exercendo efeito tóxico sobre a germinação e o desenvolvimento das espécies vegetais (ROUT et al, 2001;CUSTÓDIO et al, 2002 (ROY et al, 1988;SOUZA FILHO & DUTRA, 1998).…”
Section: Introductionunclassified